Environmental impacts at the bottom sediments in a Doce River tributary after the Fundão dam rupture (Research, Society and Development, 2020)
In 2015, the Gualaxo do Norte River basin suffered from a serious environmental disaster that affected the quality of the river environment due to the disruption of the Fundão dam structures located in Bento Rodrigues Sub-district, Mariana, Minas Gerais/ Brazil. Due to the impacts of the disaster and in view of the economic and social importance of the Gualaxo do Norte river basin, this research assessed the current situation of the river basin through sediment studies with the aim of assessing the environmental impacts caused by tailings tailings. iron ore from the rupture and other sources of pollution in the bottom sediment. To this end, water and sediment samples were collected at 27 stations throughout the Gualaxo do Norte River basin in August 2016 and January 2017, upstream (unaffected by the dam breach) and downstream of the disaster. (affected by dam tailings). The sediment results indicate that in sampling stations not affected by the disaster, metal and semimetal concentrations reflect the geology of the Iron Quadrangle. However, in the area affected by the environmental disaster, there were changes in the chemical and physical properties of the bottom sediment, especially in iron concentrations. This has reflected in contamination and iron enrichment at stations downstream of the environmental disaster.